(untitled) (Orfeu, 2020)
This article is associated with a broad research addressing musical variation, whose main objective is the systematization of the analysis through the elaboration of an original analytical model. A new version of this model proposes a formal approach based on principles of the transformational theory. The present article is focused in the notion of variation isolated from a contextual framework (that is, out of temporal perspectives), setting the basis for further explorations. .Some original concepts, like derivative work, derivative space, attributes, among others, provide means for measurement of similarity relations between referential and derived musical ideas, as well as graphic representation for these relationships.